2023
DOI: 10.2298/vsp211220037p
|View full text |Cite
|
Sign up to set email alerts
|

The Serbian version of the Brunnsviken brief quality of life scale: reliability, validity, and psychometric features among the population of high school students

Abstract: Background/Aim: Measuring of the quality of life (QoL) is very important in a daily clinical practice, because it shows significant informations as addition to symptoms. There are a large number of scales for assessment the QoL. The Brunnsviken Brief Quality of life scale (BBQ) measures importance-adjusted satisfaction across six life areas. Validation study of the BBQ scale was show a good questionnaire features (high concurrent and convergent validity, internal and test-retest reliability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The BBQ is a brief, freely available measure of subjective QoL. The current study corroborates previous findings that have shown the BBQ to be a reliable and valid measure of QoL ( Lindner et al, 2016 ; Biliunaite et al, 2021 ; Pantić et al, 2023 ). Our aim was to assess whether the factor structure of the BBQ remained stable across different age groups, genders, depressive symptom severity, and anxiety symptom severity (i.e., assess measurement invariance [MI]), and to identify potential cutoff points for the BBQ.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The BBQ is a brief, freely available measure of subjective QoL. The current study corroborates previous findings that have shown the BBQ to be a reliable and valid measure of QoL ( Lindner et al, 2016 ; Biliunaite et al, 2021 ; Pantić et al, 2023 ). Our aim was to assess whether the factor structure of the BBQ remained stable across different age groups, genders, depressive symptom severity, and anxiety symptom severity (i.e., assess measurement invariance [MI]), and to identify potential cutoff points for the BBQ.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the inclusion of importance items and the subsequent usage of weighted satisfaction ratings in the BBQ ought to be construed as a further strength of the validity of the BBQ as a marker of QoL. Previous studies have shown the BBQ to be a unifactorial measure of QoL, with good concurrent and convergent validity, high internal and test–retest reliability, and accurate classification ability in both research and clinical settings ( Lindner et al, 2016 ; Biliunaite et al, 2021 ; Pantić et al, 2023 ). In this study, the BBQ demonstrated high internal reliability during screening, Cronbach’s alpha = 0.74 [95% CI: 0.73, 0.75], indicating the BBQ to be a homogeneous scale with good internal consistency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation